Testing Efficacy of Plant Growth Regulator Products for Enhanced Winter Wheat Grain Yield and Quality - R. M. Aiken (Kansas Agricultural Experiment Station Research Reports, 2021)
Experimental plant growth regulator compounds are expected to improve wheat grain yield by extending the duration of green leaf area and altering remobilization of stored carbohydrates. In order to evaluate this, plant growth regulator materials supplied by a commercial third party were applied to Tatonka hard red winter wheat during the mid-grain fill development stage. Overall, crop productivity increased. Compared to the control treatment, two of the treatment combinations had increased grain yield (13%, machine harvest; 31%, hand harvest); increased above-ground biomass (AGB, 8%); and increased harvest index (HI, 22%). Yield components also increased, including seeds/a (21%) and seed mass (7%). Variation in chlorophyll content during the grain filling period was positively related to variation in these and other response variables.
Keywords: wheat; yield response; growth regulators